2022
DOI: 10.1098/rspb.2022.0581
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two plasmids: contributions of plasmid associated phenotypes to epidemiological success among Shigella

Abstract: Dissemination of antimicrobial resistance (AMR) genes by horizontal gene transfer (HGT) mediated through plasmids is a major global concern. Genomic epidemiology studies have shown varying success of different AMR plasmids during outbreaks, but the underlying reasons for these differences are unclear. Here, we investigated two Shigella plasmids (pKSR100 and pAPR100) that circulated in the same transmission network but had starkly contrasting epidemiological outcomes to identify plasmid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 66 publications
3
16
0
Order By: Relevance
“…The plasmid backbone encodes conjugation and stabilisation machinery and carries psiB (plasmid SOS inhibition), recently shown to inhibit the disruptive host SOS response to subminimal inhibitory concentrations of cipro oxacin. 19 Plasmids from single isolates from France and NSW also match the plasmid from the UK and searches revealed that all of these plasmids are also near identical to p893816, reported in MSM-associated CipR.MSM5 S. sonnei in London in 2020, 64 and perhaps more strikingly Plasmid 3 from an Australian S. exneri 3a isolated in 2018 (Table 2, Supplementary Fig. 1B).…”
Section: International Linkage and Accessory Genome Evolution Of The ...mentioning
confidence: 68%
See 4 more Smart Citations
“…The plasmid backbone encodes conjugation and stabilisation machinery and carries psiB (plasmid SOS inhibition), recently shown to inhibit the disruptive host SOS response to subminimal inhibitory concentrations of cipro oxacin. 19 Plasmids from single isolates from France and NSW also match the plasmid from the UK and searches revealed that all of these plasmids are also near identical to p893816, reported in MSM-associated CipR.MSM5 S. sonnei in London in 2020, 64 and perhaps more strikingly Plasmid 3 from an Australian S. exneri 3a isolated in 2018 (Table 2, Supplementary Fig. 1B).…”
Section: International Linkage and Accessory Genome Evolution Of The ...mentioning
confidence: 68%
“…18 The acquisition of resistance against recommended treatments for shigellosis and other STIs is a global public health concern, heralding an increased risk of treatment failure, and the emergence of pan-drug resistance (PDR) in S. sonnei. 70 Given the global transmission of the low the tness cost MDR pKSR100-type plasmids among various serotypes of Shigella, 19 we predict that the ESBL plasmid p893916, and others like it, will continue to spread via horizontal gene transfer to other species and serotypes of Shigella in MSM. Alternatively -or concurrently -other species and serotypes of Shigella could follow a similar journey of stepwise accumulation of AMR determinants, resulting in the acquisition of resistance to third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations